How do undergraduates perceive the use of assessment? A study in higher education - Pereira, Diana (2022)
Drawing upon a wider piece of research, this paper focuses on the validation of a ‘use of assessment’ scale in five Portuguese public universities with 5549 students. The study aims to investigate the psychometric properties of the scale, to describe how students look at assessment uses, to analyse their utility perceptions of assessment, and to understand their perspectives regarding participation in the assessment process. The scale demonstrated adequate validity and reliability based on factor analysis of the internal structure. Preference for alternative methods of assessment was negatively correlated with a preference for traditional methods of assessment. However, preference for alternative methods was correlated with higher scores for assessment effectiveness, fairness and level of participation and engagement with assessment. On the contrary, preference for traditional methods was negatively correlated with perceived fairness and with engagement with assessment.